2021
DOI: 10.3390/jcm10102143
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of High-Intensity Interval Training Periods on Morning Serum Testosterone and Cortisol Levels and Physical Fitness in Men Aged 35–40 Years

Abstract: Background: Intensive physical activity largely modulates resting concentrations of blood cortisol (C) and testosterone (T) and their molar ratio, which is defined as the anabolic–catabolic index and expressed as T/C × 102. The aim of the study is to evaluate the effect of the author’s high-intensity training program on T, C, T/C × 102, and selected physical fitness indices in men between 35 and 40 years of age. Methods: The experiment was conducted on a group of 30 healthy men, divided into control and experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 46 publications
4
7
0
Order By: Relevance
“…As seen in previous studies, training adaptations seem to reduce the sensitivity of cortisol in individuals. 25,29 Similar results were observed by Ambrozy et al 42 who examined a decrease in the cortisol levels of men between the ages of 35-40 years old. The men performed eight weeks of HIIT and RT and demonstrated a more balanced testosterone/cortisol ratio.…”
Section: Open Access Journal Of Exercise and Nutritionsupporting
confidence: 81%
See 1 more Smart Citation
“…As seen in previous studies, training adaptations seem to reduce the sensitivity of cortisol in individuals. 25,29 Similar results were observed by Ambrozy et al 42 who examined a decrease in the cortisol levels of men between the ages of 35-40 years old. The men performed eight weeks of HIIT and RT and demonstrated a more balanced testosterone/cortisol ratio.…”
Section: Open Access Journal Of Exercise and Nutritionsupporting
confidence: 81%
“…An increase in testosterone indicated which training adaptation occurred and resulted in a blunting or loss in cortisol sensitivity. 25,42…”
Section: Open Access Journal Of Exercise and Nutritionmentioning
confidence: 99%
“…It is advisable for athletes to strive to increase their T/C ratio to optimize muscle protein metabolism and promote muscle growth during exercise ( 63 ). A significant decrease in the T/C index may indicate that the training intensity is too high for inexperienced horses, thus catabolic processes are prevailing, potentially leading to a decrease in skeletal muscle mass in extreme cases ( 55 ). Some research in humans has shown that there are no differences in the T/C ratio 12 h following high-intensity interval training (20 min of 15 s intervals of running at 110% of maximum oxygen consumption interspersed with 15 s of active rest at 40% of maximum oxygen consumption) ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing body of research indicating the usefulness of the testosterone-to-cortisol (T/C) ratio as a marker of physical fitness in humans (55)(56)(57)(58). It was postulated that the T/C ratio is more sensitive to the stress of training than either T or C measures alone.…”
Section: T/c Ratiomentioning
confidence: 99%
“…Both interventions significantly evaluated testosterone level at post-HIIT, but after 30 min recovery, 20 min HIIT maintained higher level of testosterone than 30 min HIIT. Since testosterone shows anabolic effects and cortisol promotes catabolic effects, the T/C has been considered as a signal of the training activity is too high and catabolic processes prevail ( Ambroży et al, 2021 ). T/C is correlated with the duration and intensity of training, T/C decline indicates that the body is under high metabolic stress and accumulates fatigue ( Turner et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%